Machine learning-based permeability prediction for CO₂ storage: A case study from the Petrel Sub-basin, Australia - Muhammad Faisal Waqar; Shengwen Qi; Songfeng Guo; Zan Wang; Bowen Zheng; Manawar Pervaiz (Geomechanics for Energy and the Environment, 2026)

Recent developments in design and fabrication of ZIF-based materials for CO2 mitigation and environmental remediation - Hafsa Khalid; Aimon Saleem; Umer Younas; Parveen Akhter; Heena Ameen; Faisal Ali; M.I. Khan; Muhammad Pervaiz (Journal of Environmental Management, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

“Ondansetron augmentation for obsessive–compulsive disorder: A systematic review and meta-analysis of randomized placebo-controlled trials” - Anas Mohammad; Mohammad Ibrahim; Aneeq Mahmood Khan; Usama Pervaiz; Sarah Aijaz; Muhammad Hassnain Nasrullah; Hammad Jamil (European Journal of Clinical Pharmacology, 2026)

Advances in fulvic acid extraction from lignite: techniques, challenges, and applications - Iqra Yousaf; Lizhen Gao; Iffat Riaz; Sidra Pervaiz; Muhammad Usman (Environmental Monitoring and Assessment, 2026)

Evaluation of resistance level of exotic cotton Gossypium hirsutum accession “Mac-07” against cotton leaf curl disease complex - Khalid Pervaiz Akhtar; Sajawal Iqbal; Najeeb Ullah; Muhammad Qasim Aslam; Muhammad Kashif Riaz Khan; Imran Amin (Journal of Plant Pathology, 2026)

Evaluation of [Emim]Glu ionic liquid as a deconstruction solvent for lignocellulosic biomass to biobased materials - Pervaiz Ahmad; Awais Khalid; Abdulhameed Khan; Nawshad Muhammad (Biomass and Bioenergy, 2026)

Performance comparison of complete mix reactor and static mixer in ballasted flocculation - Muhammad Qasim; Muhammad Naveed Afridi; Salman Ali Suhail; Usman Pervaiz Khan; Imtiaz Afzal Khan; Jong-Oh Kim (Chemosphere, 2025)

Growth phenology, cambial activity, and formation of secondary vascular tissues in Juniperus procera trees - Pervaiz R. Khan; Rahmah N Al-Qthanin; Ibrahim M. Aref; Muhammad Iqbal (Flora, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Enhancing food safety with zirconium-based electrochemical sensors: A comprehensive review - Muhammad Hussnain Afzal; Wajeeha Pervaiz; Zhuo Huang; Nomair Elahi; You Xu; Guangfang Li; Shufang He; Yuan Xiang; Hongfang Liu (Food Chemistry, 2025)

Micro and Nanoplastics in Ecosystems: Interrelated Sources, Risks, Pathways, Consequences, Mitigation, Challenges and Future Recommendations - Tauqeer Hussain; Muhammad Summer; Shaukat Ali; Rana Rashad Mahmood Khan; Muhammad Pervaiz; Zohaib Saeed (Water, Air, & Soil Pollution, 2025)

Biocompatible Nitro Group-Based Photosensitizer for AIE, Hypoxia, and Photodynamic Therapy. Experimental and Theoretical Approach - Maryam Rana; Munaza Pervaiz; Muhammad Arif Ali; Muhammad Ahmad; Laiqi Zhang; Shengnan Yin; Tansir Ahamad; Mansoor Akhtar (Journal of Fluorescence, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the therapeutic potential of Ixora extract: a comprehensive review of mediated studies - Rabiyah Nadeem; Muhammad Imran; Zohaib Saeed; Muhammad Pervaiz; Umer Younas (Advances in Traditional Medicine, 2025)

Machine learning-enhanced electrochemical sensors for food safety: Applications and perspectives - Wajeeha Pervaiz; Muhammad Hussnain Afzal; Niu Feng; Xuewen Peng; Yiping Chen (Trends in Food Science & Technology, 2025)

Retraction notice to “A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites” [Fuel 336 (2023) 126930] - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

Pyocins and Beyond: Exploring the World of Bacteriocins in Pseudomonas aeruginosa - Muhammad Suleman; Allah Rakha Yaseen; Shahbaz Ahmed; Zoha Khan; Asma Irshad; Afsah Pervaiz; Hafiza Hiba Rahman; Muteeba Azhar (Probiotics and Antimicrobial Proteins, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Removal of chlorpyrifos from aqueous medium using Ca-CuO@clay nanoflakes coated with deep eutectic solvent - Abdullah Zia; Umer Younas; Zahid Ali; Rabia Nazir; Faisal Ali; Aemin Irfan; Muhammad Pervaiz (Environmental Monitoring and Assessment, 2024)

Retraction Note: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Microbial goldmine: Investigating probiotic floral diversity in human breast milk - Ayesha Saeed; Azra Yasmin; Mehreen Baig; Maryam Pervaiz; Muhammad Arslan Ahmed; Muhammad Tabish; Humaira Hashmat (Bioactive Carbohydrates and Dietary Fibre, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Plant-mediated green synthesis of silver nanoparticles: Synthesis, characterization, biological applications, and toxicological considerations: A review - Zarfishan Zulfiqar; Rana Rashad Mahmood Khan; Muhammad Summer; Zohaib Saeed; Muhammad Pervaiz; Shahzad Rasheed; Behram Shehzad; Fatima Kabir; Saira Ishaq (Biocatalysis and Agricultural Biotechnology, 2024)

Temporal profiling of physiological, histological, and transcriptomic dissection during auxin-induced adventitious root formation in tetraploid Robinia pseudoacacia micro-cuttings - Saleem Uddin; Muhammad Zeeshan Munir; Eduardo Larriba; José Manuel Pérez-Pérez; Sadia Gull; Tariq Pervaiz; Umer Mahmood; Zahid Mahmood; Yuhan Sun; Yun Li (Planta, 2024)

Influence of Phosphate Solubilizing Bacteria on the Growth of mustard Grown Under Drought Stress Conditions - Farhat Suhail; Aftab Afzal; Laraib Naseer; Aneela Pervaiz; Muhammad Ikram; Summaira Shaheen; Yasir Islam; Naeem Khan (Agricultural Research, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Role of renewable and non-renewable energy consumption in environmental quality and their subsequent effects on average temperature: an assessment of sustainable development goals in South Korea - Waqar Ali Ather Bukhari; Amber Pervaiz; Mahwish Zafar; Muhammad Sadiq; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Hydrothermal synthesis of V2O5/TiO2 decorated graphitic carbon nitride nanocomposite for biomolecule oxidation inhibition and dye degradation applications - Muhammad Waseem; Awais Ahmad; Muhammad Sagir; Umer Younas; Zohaib Saeed; Muhammad Pervaiz; Faisal Ali; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Rama Rao Karri (Environmental Research, 2023)

“Garlic and ginger extracts mediated green synthesis of silver and gold nanoparticles: A review on recent advancements and prospective applications’’ - Zohaib Saeed; Muhammad Pervaiz; Anam Ejaz; Shah Hussain; Shumila Shaheen; Behram Shehzad; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Groundwater quality risk assessment using hydro-chemical and geospatial analysis - Hafiz Umar Farid; Hafiz Usman Ayub; Zahid Mahmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Rana Muhammad Asif Kanwar; Muhammad Mubeen; Pervaiz Sakinder (Environment, Development and Sustainability, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

RETRACTED: A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2023)

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

Green synthesis of graphene-based metal nanocomposite for electro and photocatalytic activity; recent advancement and future prospective - Shumila Shaheen; Zohaib Saeed; Awais Ahmad; Muhammad Pervaiz; Umer Younas; Rana Rashad Mahmood Khan; Rafael Luque; Saravanan Rajendran (Chemosphere, 2023)

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

RETRACTED ARTICLE: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Low-Carbon Materials: Genesis, Thoughts, Case Study, and Perspectives - Seeram Ramakrishna; Muhammad Pervaiz; Jimi Tjong; Patrizia Ghisellini; Mohini M Sain (Circular Economy and Sustainability, 2022)

Rhizobacterial, Fusarium Complex, and Fungicide Seed Treatments Regulate Shoot and Root Traits of Soybean Plants - Anthony Adesemoye; Zahida H. Pervaiz; Lipi Parikh; Srikanth Kodati; Qingming Zhang; Strahinja Stepanović; Muhammad Saleem (Journal of Soil Science and Plant Nutrition, 2021)

Identification of GH17 gene family in Vitis vinifera and expression analysis of GH17 under various adversities - Tariq Pervaiz; Tianhua Liu; Xiang Fang; Yanhua Ren; Xiyang Li; Zhongjie Liu; Muhammad Fiaz; Jinggui Fang; Lingfei Shangguan (Physiology and Molecular Biology of Plants, 2021)

Correction to: Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Asphodelus tenuifolius extracts arrested inflammation and arthritis through modulation of TNF-α, NF-κB, ILs, and COX-2 activities in in vivo models - Mohammad Saleem; Anam Iftikhar; Muhammad Asif; Khalid Hussain; Alamgeer; Pervaiz Akhtar Shah; Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Tanzeem; Hafiza Sidra Yaseen (Inflammopharmacology, 2021)

Exploring the role of fossil fuels, hydroelectricity consumption, and financial sector in ensuring sustainable economic development in the emerging economy - Faisal Faisal; Muhammad Numan Khan; Ruqiya Pervaiz; Peshraw Majid Muhamad; Mohammad Othman Jamil Rashdan (Environmental Science and Pollution Research, 2021)

Date palm rachis as a raw material for wood composite industry: anatomical characteristics - Pervaiz Rasheed Khan; Said Saad Hegazy; Muhammad Iqbal (Brazilian Journal of Botany, 2020)

GIS-based assessment of aridity over Punjab Province, Pakistan, by using climatic indices - Kanwal Javid; Muhammad Ameer Nawaz Akram; Maria Mumtaz Ranjha; Shazia Pervaiz (Arabian Journal of Geosciences, 2020)

Characterization of tomato mosaic virus and search for its resistance in Solanum species - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Mudasser Habib (European Journal of Plant Pathology, 2019)

First report of molecular characterization of Aspergillus flavus from maize in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Syed Wajih ul Hassan; Muhammad Rafique Asi; Yumna Sadef (Journal of Plant Pathology, 2019)

Evaluation of tomato genotypes for early blight disease resistance caused by Alternaria solani in Pakistan - Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Yussouf Saleem; Qumer Iqbal; Muhammad Asghar; Abdul Rehman Khan (Journal of Plant Pathology, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

First report of Macrophomina phaseolina causing dry root rot of lentil in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Jawad Asghar; Ghulam Abbas (Journal of Plant Pathology, 2019)

Characterization of Vv-miR156: Vv-SPL pairs involved in the modulation of grape berry development and ripening - Mengjie Cui; Chen Wang; Wenying Zhang; Tariq Pervaiz; Muhammad Salman Haider; Wei Tang; Jinggui Fang (Molecular Genetics and Genomics, 2018)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Synthesis, computational studies and biological evaluation of new 1-acetyl-3-aryl thiourea derivatives as potent cholinesterase inhibitors - Aamer Saeed; Muhammad Shakil Shah; Fayaz Ali Larik; Shafi Ullah Khan; Pervaiz Ali Channar; Ulrich Flörke; Jamshed Iqbal (Medicinal Chemistry Research, 2017)

Functional Analysis of VvBG1 During Fruit Development and Ripening of Grape - Haifeng Jia; Chen Wang; Cheng Zhang; Muhammad Salman Haider; Pengcheng Zhao; Zhongjie Liu; Lingfei Shangguan; Tariq Pervaiz; Jinggui Fang (Journal of Plant Growth Regulation, 2016)

Modulation of antioxidant enzymes in Juniperus procera needles in relation to habitat environment and dieback incidence - Ibrahim M. Aref; Pervaiz R. Khan; Salim Khan; Hashim El-Atta; Abdalla I. Ahmed; Muhammad Iqbal (Trees, 2016)

Response of Datura innoxia Linn. to Gamma Rays and Its Impact on Plant Growth and Productivity - Ibrahim M. Aref; Pervaiz R. Khan; Abdulaziz A. Al Sahli; Azamal Husen; M. K. A. Ansari; Mahmooduzzafar; Muhammad Iqbal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Genetic analysis of a consanguineous Pakistani family with Leber congenital amaurosis identifies a novel mutation in GUCY2D gene - MUZAMMIL AHMAD KHAN; VERENA RUPP; MUHAMMAD AYAZ KHAN; MUHAMMAD PERVAIZ KHAN; MUHAMMAD ANSAR; CHRISTIAN WINDPASSINGER (Journal of Genetics, 2014)

Drought-induced adaptive changes in the seedling anatomy of Acacia ehrenbergiana and Acacia tortilis subsp. raddiana - Ibrahim M. Aref; Abdallah I. Ahmed; Pervaiz R. Khan; Hashim A. El-Atta; Muhammad Iqbal (Trees, 2013)

Resistance of Solanum species to Cucumber mosaic virus subgroup IA and its vector Myzus persicae - Khalid Pervaiz Akhtar; Muhmmad Yussouf Saleem; Muhammad Asghar; Mushtaq Ahmad; Nighat Sarwar (European Journal of Plant Pathology, 2010)

Papillary thyroid cancer in a patient with MUTYH-associated polyposis (MAP) - Muhammad Ali Pervaiz; Amanda Eppolito; Karen Schmidt (Familial Cancer, 2010)

Correlative evidence for peroxidase involvement in disease resistance against Alternaria leaf blight of tomato - Amjad Hameed; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Muhammad Asghar (Acta Physiologiae Plantarum, 2010)